Study of low-pressure discharge by optical emission spectroscopy - Afanasіeva, I.A.; Afanasiev, S.N.; Bobkov, V.V.; Gritsyna, V.V.; Mahotka, I.S.; Okseniuk, I.I.; Shevchenko, D.I.; Skrypnyk, A.O. (Вопросы атомной науки и техники, 2020)
The axial distribution of excited argon and tungsten atoms in plasma of direct current magnetron discharge in crossed fields have been analyzed by optical emission spectroscopy. The influence of discharge parameters (discharge current I, buffer gas pressure pAr and zone of discharge glow Δl) and excited states energy E* of studied particles on the axial distribution Ar and W atoms have been observed. The assumption about the excitation processes in the magnetron plasma is given. Методом оптичної емісійної спектроскопії проаналізовано аксіальний розподіл збуджених атомів аргону і вольфраму в плазмі постійного магнетронного розряду в схрещених E×H-полях. Виявлено вплив параметрів розряду (струм розряду Id, тиск буферного газу pAr і область світіння розряду Δl) та енергії збуджених станів E* досліджуваних частинок на розподіл атомів Ar і W уздовж осі розряду. Зроблено припущення про процеси збудження в магнетронній плазмі. Методом оптической эмиссионной спектроскопии проанализировано аксиальное распределение возбуж- денных атомов аргона и вольфрама в плазме постоянного магнетронного разряда в скрещенных E×H-полях. Обнаружено влияние параметров разряда (ток разряда Id, давление буферного газа pAr и область свечения разряда Δl) и энергии возбужденных состояний E* исследуемых частиц на распределение атомов Ar и W вдоль оси разряда. Сделано предположение о процессах возбуждения в магнетронной плазме.